Immunoinformatics-guided selection of immunogenic peptides from betanodavirus induce antigen-specific antibody production in hybrid grouper, Epinephelus fuscoguttatus x Epinephelus lanceolatus - Yusoff, Syasya Binti; Baharum, Syarul Nataqain Binti; Omar, Mohd Shahir Shamsir Bin; Chong, Chou Min; Lee, Po-Tsang; Azmi, Fazren; Low, Chen Fei (Elsevier, 2023)
Betanodavirus is a significant pathogen that causes viral nervous necrosis (VNN) in a wide range of fish species. It could cause up to 100 mortality in the infected farmed fish, especially at the larval stage. Red-Spotted Grouper Nervous Necrosis Virus (RGNNV), one of the betanodavirus genotypes, has been proven to have a wide range of host-compatibility across warm-water fish species. To date, there is no viable strategy to combat this virus infection, but vaccination approach is known to be effective against infectious diseases. Thus, current study aimed to identify immunogenic peptides as potential subunit vaccine candidates against grouper betanodavirus. Nucleotide sequences of the grouper nervous necrosis virus were retrieved from the National Center for Biotechnology Information database. B- and T-cell epitopes were predicted using the Immune Epitope Database analysis resource and the NetCTL 1.2 server, respectively. The predicted B- and T-cell epitopes were analysed for its respective antigenicity, immunogenicity, physico-chemical properties, and surface accessibility. Selected epitopes were then synthesized for immunization assay to examine antigen-specific antibody production in the immunized grouper. Five epitopes (one B-cell and four T-cell epitopes) were selected based on the immunogenicity score. The B-cell epitope has the highest immunogenicity score of 0.9333. Physico-chemical properties analysis of the B-cell epitope shown highest GRAVY score of 0.516 and was predicted to possess the longest estimated half-life of 30 h. Structural analysis has shown that the B-cell epitope possesses the largest accessible surface on the virus particle. Immunization of grouper with the selected B-cell epitope induced the highest antigen-specific antibody production as compared to grouper that was immunized with the selected T-cell epitope. This study demonstrated the feasibility of reverse vaccinology approach in the selection and design of immunogenic peptides against NNV in grouper to serve as the potential vaccine candidate. © 2023 Elsevier B.V.